Notes on Raymond Chandler's "Red Wind" - Seals, Marc (Eureka College, 2008)
Raymond Chandler's 1938 short story "Red Wind" is an excellent example of Chandler's short fiction, as it contains most of Chandler's signature elements. Additionally, "Red Wind" may be effectively used in the undergraduate classroom as a text for teaching literary analysis.
Keywords: John Dalmas; Philip Marlowe; Short Stories; Noir; Crime Fiction; Detective Fiction; Raymond Chandler